Twitter: High on celebrity gossip, low on news discussion - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2012)
The news media are going through their most robust transformation since the dawn of the printing press, in large part due to the Internet and message sharing services like Twitter. As news agencies gear up to find out how they can make use of social media, businesses have also wondered how tapping on this new phenomenon can help them increase their customer reach. The first step to doing it is to understand the information sharing habits of these users.